PENGARUH BERKUMUR DENGAN LARUTAN EKSTRAK KULIT NANAS (Ananas comosus(L)Merr) TERHADAP pH SALIVA RONGGA MULUT - Minarni Minarni; Dewi Rosmalia (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2022)
Background: Saliva acts as a buffer system to maintain the optimal pH of the mouth. The acidic pH of saliva causes demineralization of enamel resulting in dental caries. The bromelain enzyme found in pineapple skin can increase the pH of saliva by inhibiting bacterial growth. This study aims to determine the effect of gargling with pineapple peel extract solution (Ananas comosus(L) Merr) on salivary pH in students of SMPN 3 Bukit Apit. Methods: This study was using a quasi-experimental method with a pre-test and post-test without a control group design. The research sample was 27 students of SMPN 3 Bukit Apit. The sample was divided into 3 groups of 9 students eacof h who met the inclusion criteria. Group 1 rinsed with 25% pineapple peel extract, growas up 2 rinsed with 50% pineapple peel extract, solution and group 3 rinsed with distilled water. Salivary pH was measured using a digital pH meter before rinsing, after rinsing for 3 minutes, after rinsing for ,15 minutes and after rinsing for 30 minutes. Data were analyzed by t Test followed by ANOVA test Results: There was a significant effect (p<0.005) of gargling with pineapple peel extract solution on the pH of saliva. The concentration of the pineapple peel extract solution that had the most effect on salivary pH was the concentration of 50%. Conclusion: Gargling with a solution of pineapple peel extract can increase the pH of oral saliva.